2012
DOI: 10.1074/jbc.m112.365056
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Vertebrate Amino Sugars with N-Glycolyl Groups

Abstract: Background:The sialic acid N-glycolylneuraminic acid (Neu5Gc) shows conserved suppression of expression in vertebrate brains, suggesting brain-specific toxicity. Results: ␣2-8-Linked Neu5Gc incorporated into the neural glycan polysialic acid (polySia) resists sialidase breakdown through conformational effects. Conclusion: Neu5Gc in brain would prevent rapid turnover of surface polySia. Significance: This mechanism potentially underlies the evolutionary suppression of Neu5Gc expression in vertebrate brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 105 publications
5
28
1
Order By: Relevance
“…Unlike the highly variable levels of Neu5Gc found in all other tissues, the suppression of brain Neu5Gc expression is remarkably conserved across all vertebrates that have been studied to date (see Table 1, reproduced from [32]). The highest published fraction of Neu5Gc in brain tissue is 10% in a sample of adult bovine neocortex and 5% in calf [33].…”
Section: Rarity Of Neu5gc In the Vertebrate Brainmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike the highly variable levels of Neu5Gc found in all other tissues, the suppression of brain Neu5Gc expression is remarkably conserved across all vertebrates that have been studied to date (see Table 1, reproduced from [32]). The highest published fraction of Neu5Gc in brain tissue is 10% in a sample of adult bovine neocortex and 5% in calf [33].…”
Section: Rarity Of Neu5gc In the Vertebrate Brainmentioning
confidence: 99%
“…It is interesting to note here that polysialyltransferases are able to incorporate a number of unnatural sialic acids into polySia [101, 102]. Recently, our laboratory has demonstrated that cells from a murine neuroblastoma line are similarly able to incorporate Neu5Gc into endogenous polySia [32]. Although polymers of Neu5Gc are found in the glycoproteins of the eggs of salmonid fish [103], Neu5Gc has never been reported in mammalian polysialic acid, neural or otherwise.…”
Section: Claims For Presence Of Neu5gc In Neural Tissuesmentioning
confidence: 99%
See 3 more Smart Citations